2020
DOI: 10.1039/c9py01868a
|View full text |Cite
|
Sign up to set email alerts
|

The construction of photoresponsive polymer particles with supramolecular helicity from achiral monomers by helix-sense-selective polymerization

Abstract: Optically active azobenzene-containing polymer particles successfully prepared from achiral monomers for the first time by helix-sense-selective dispersion polymerization, also known as asymmetric helix-chirogenic polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Many studies have shown that when a chiral solvent is introduced into an achiral polymer system, the van der Waals forces, CH/π interactions, dipole interactions, metal-ligand coordination, etc., can induce the formation of optically active polymer aggregates. [79,128,129] In 2010, our group presented the synthesis of achiral polymer poly[(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-4,4ʹazobenzene] (F8AZO). It could assemble into optically active aggregates in mixed solvent containing chiral limonene, which showed obvious aggregation ICD.…”
Section: Chiral Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that when a chiral solvent is introduced into an achiral polymer system, the van der Waals forces, CH/π interactions, dipole interactions, metal-ligand coordination, etc., can induce the formation of optically active polymer aggregates. [79,128,129] In 2010, our group presented the synthesis of achiral polymer poly[(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-4,4ʹazobenzene] (F8AZO). It could assemble into optically active aggregates in mixed solvent containing chiral limonene, which showed obvious aggregation ICD.…”
Section: Chiral Solventmentioning
confidence: 99%
“…Many studies have shown that when a chiral solvent is introduced into an achiral polymer system, the van der Waals forces, CH/π interactions, dipole interactions, metal–ligand coordination, etc., can induce the formation of optically active polymer aggregates. [ 79,128,129 ]…”
Section: Construction and Regulation Of Supramolecular Chirality In P...mentioning
confidence: 99%
“…As far as HSSP is concerned, it is widely explored in asymmetric polymerization for preparing chiral helical polymers starting from achiral monomers. [ 184,185 ] Diverse strategies can be taken to induce the otherwise racemic helical polymer chains to form one homohelicity or one predominant helicity. These strategies include using chiral catalyst, chiral monomer‐achiral monomer copolymerization, chiral field, and chiral postinduction.…”
Section: Construction Of Chiral Graphene Hybrid Materialsmentioning
confidence: 99%
“…Wu et al developed a novel synthetic strategy for the preparation of optically active helical polyisocyanides by using an achiral initiator in the presence of a chiral additive [ 54 ]. Recently, our group presented a helix-sense selective dispersion polymerization (HSSDP) strategy for preparing optically active monodisperse Azo-containing polymer particles with supramolecular chirality for the first time [ 55 ]. Generally, the term “ M / P helicity” of helical chirality is usually used in helical systems [ 17 ].…”
Section: Basic Concepts Related To Supramolecular Chiralitymentioning
confidence: 99%